Exploring modalities of rhetorical moves in Malaysian travel brochures through multimodal analysis - Al-Najhi, Ahlam Muhammed; Mohd Kasim, Zalina; Darmi, Ramiza; Sharmini, Sharon; Zaidan, Musaab Alaa (Universiti Putra Malaysia, 2025)
Rhetorical moves refer to text segments employed to communicate a specific purpose effectively. Despite the extensive body of research on the significance of rhetorical moves as a crucial strategy in various genres, the phenomenon of visual shapes such as texts, images, colors, logos, icons, and infographics of moves that sometimes replace the text remains unexplained. The study's objective is to uncover the interplay of visual modalities in the formation of the rhetorical moves found in Malaysian travel brochures. The study employs a multimodal analysis method: Bhatia's (1993–2004) model of Structural Move Analysis was employed to identify the moves in textual modes, and Bateman's (2008) Genre and Multimodality model was employed to identify the moves’ visual and graphical modes. During the annual MATTA Fair event in Kuala Lumpur, a collection of 15 travel brochures was obtained, amounting to a total of 39 pages. The findings of the study demonstrate a complex interaction between textual and graphical components. Notably, the study revealed that both textual and graphical modes play a crucial role in shaping rhetorical moves, with a nearly equal proportion observed between the two. The findings presented in this study offer novel insights into the visual presence and modern textuality of rhetorical moves.